Platinum adsorption from chloride media using carbonized biomass and commercial sorbent - (:unkn) unknown (SOC MINING METALLURGY EXPLORATION INC, 2013)
Pistachio nut shells, an agricultural waste biomass, and Lewatit TP 214, a commercial sorbent, were investigated as adsorbents for the adsorption of platinum from dilute hexachloroplatinic acid solutions. Before the pistachio nut shells were carbonized, adsorption percentage was 65%, whereas Lewatit TP 214 ensured almost 100% adsorption. However, after the pistachio nut shell was carbonized at 1,000 degrees C under an argon atmosphere, the platinum adsorption (%) increased two-fold. The effects of such parameters as sorbent dosage, contact time, temperature and solution pH on adsorption were studied in detail in batch mode. The adsorption equilibrium data were best fitted with the Langmuir isotherm model. The maximum adsorption capacities, Q(max), at 25 degrees C were found to be 38.31 and 33.22 mg/g for the carbonized pistachio nut shell and Lewatit TP 214, respectively. The adsorption of platinum on both sorbents was found to be described by the pseudo-second-order kinetic model. The results indicated that the activated carbon prepared from pistachio nut shells can be effectively used for the removal of platinum from acidic solutions.
Keywords: Adsorption; Platinum; Activation; Pistachio nut shells; Chloride; LINKED CHITOSAN RESIN; PISTACHIO-NUT SHELLS; ACTIVATED CARBONS; AQUEOUS-SOLUTIONS; RICE HUSK; PALLADIUM(II); GOLD(III); STONE; IONS; ASH